P‐184: Numerical Analysis of QCW‐Laser‐Based Spot‐Beam Crystallization of Si Films. Issue 1 (2nd June 2017) - Pan, Wenkai; Song, Ruobing; Suresh, Akhilesh K.; Wong, Vernon K.; Yu, Miao; Choi, Insung; Im, James S.
Abstract : We are in the process of developing a new laser annealing method referred to as Spot‐Beam Crystallization (SBC). The SBC method, which is potentially well suited for manufacturing advanced ultra‐high‐resolution AMOLED displays, is most effectively implemented using ultra‐high‐frequency quasi‐continuous‐wave (QCW) pulsed lasers. Conceptually and physically, this QCW‐laser‐based SBC (Q SBC) approach builds on a thermally additive utilization of multiple short‐lived ultra‐high‐frequency pulses, achieved via overlapped scanning of a small spot beam to incrementally and gradually heat and melt the beam‐irradiated region. Using an updated version of a previously developed numerical program, we have carried out a simulation‐based investigation to quantitatively examine and evaluate the basic tenets of the approach relevant specifically to partial‐melting‐based "ELA‐like" crystallization of small‐columnar‐grained polycrystalline Si films using the Q‐SBC method. The results from the effort to date as reported in this paper (1) largely confirm and validate the viability of the Q‐SBC approach, and (2) suggest some specific directions for optimal development of the Q‐SBC equipment and process.